Evaluation of the mechanical performance recovery of self-healing cementitious materials – its methods and future development: A review. (10th July 2019) - Wang, X.F.; Yang, Z.H.; Fang, C.; Han, N.X.; Zhu, G.M.; Tang, J.N.; Xing, F.
Highlights: The healing mechanisms and performance of self-healing methods are reviewed. Test methods on evaluation and characterization of self-healing efficiency. Challenges and further development on healing materials and encapsulation methods. Abstract: The healing mechanisms and healing performance of cementitious materials are reviewed, including autogenic self-healing and bacteria-based self-healing, as well as the use of mineral admixtures, polymeric adhesive agents, superabsorbent polymers, and shape memory materials. To determine the robustness of various self-healing methods, several reliable methods for the assessment of the healing efficiency are reviewed in terms of the mechanical properties. In addition, a comprehensive review of the applicable techniques is provided, i.e., microscopy, spectroscopy, thermoanalysis, and imaging for the characterization of the healing products, the microstructure, and the healing process. To demonstrate the applicability of various self-healing methods in engineering practice, the major disadvantages and challenges of the self-healing materials and encapsulation techniques are reviewed and the future development in the field of self-healing cementitious materials is addressed. Finally, an engineering case study on the healing efficiency of cementitious materials for four self-healing systems is discussed.